Advances in the etiology and neuroimaging of children with attention deficit hyperactivity disorder - Shen, Fang; Zhou, Hui (Frontiers in Pediatrics, 2024)
Attention deficit hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder in children, characterized by age-inappropriate inattention, hyperactivity, and impulsivity, which can cause extensive damage to children's academic, occupational, and social skills. This review will present current advancements in the field of attention deficit hyperactivity disorder, including genetics, environmental factors, epigenetics, and neuroimaging features.Simultaneously, we will discuss the highlights of promising directions for further study.